A decline of LAMP- 2 predicts ursodeoxycholic acid response in primary biliary cirrhosis - Wang, Lu (Sci Rep, 2015)
Biochemical response to ursodeoxycholic acid (UDCA) in patients with primary biliary cirrhosis (PBC) is variable. We have previously reported that augmented expression of lysosome-associated membrane protein 2 (LAMP-2) was correlated with the severity of PBC. This study aimed to determine whether serum LAMP-2 could serve as a predictor of biochemical response to UDCA. The efficiency of serum LAMP-2 to predict biochemical response was assessed after 1 year of UDCA treatment in PBC patients by a retrospective analysis. We found that the basal serum LAMP-2 level was increased in PBC, especially in patients with stage III-IV (p = 0.010) or TBIL > 1 mg/dL (p = 0.014). Baseline serum LAMP-2 was higher in non-responders than that in responders, but the difference was statistically insignificant. However, after UDCA treatment, serum LAMP-2 level decreased prominently in the first 3 months, which was more obvious in responders. Further studies showed that the 35% decline of LAMP-2 after treatment for 3 months could be stated as an indicator of UDCA response with the sensitivity of 62.9% and specificity of 75.0% by Paris criteria. Meanwhile the specificity and sensitivity were identified as 63.5% and 64.1% by Barcelona criteria. Together, a decline in LAMP-2 might help to predict the response to UDCA.